2019
DOI: 10.3390/nu11122955
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Interventions for Gout and Effect on Cardiovascular Risk Factors: A Systematic Review

Abstract: Gout is one of the most prevalent inflammatory rheumatic disease. It is preceded by hyperuricemia and associated with an increased risk for cardiovascular disease, both related to unhealthy diets. The objective of this systematic review is to better define the most appropriate diet addressing both disease activity and traditional cardiovascular risk factors in hyperuricemic patients. We included clinical trials with patients diagnosed with hyperuricemia or gout, investigating the effect of dietary intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 38 publications
0
32
0
3
Order By: Relevance
“…Today there is no clear evidence that lifestyle modification might be effective in decreasing SUA levels: insofar as a low-energy Mediterranean diet aimed at achieving optimal body weight seems reasonably the best approach [ 113 ]. Single nutrients and food have been associated with impaired or improved SUA levels, but definite data are yet lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Today there is no clear evidence that lifestyle modification might be effective in decreasing SUA levels: insofar as a low-energy Mediterranean diet aimed at achieving optimal body weight seems reasonably the best approach [ 113 ]. Single nutrients and food have been associated with impaired or improved SUA levels, but definite data are yet lacking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies found that the risk of gout was inversely associated with consumption of coffee and omega-3 fatty acids, both of which decreased DNA methylation [ 58 61 ]. Conversely, legumes, which increased methylation, reduced the risk of gout [ 62 , 63 ]. Additional studies are needed to identify other environmental factors that might impact gout by increasing or decreasing DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the protocol of stretching exercises was developed based on recommendations from the Guidelines for Exercise Testing and Prescription proposed by the American College of Sports Medicine (39). When encountering medical related scenarios with self-reported hyperthyroidism, hyperuricemia, or urinary stones, the servicelearning students consulted supervisors, who were experienced registered nurses, regarding foods not to recommend and/or increase in amount, such as iodine-rich foods (40,41), purinerich foods (42,43), and diets high in salt, purine, and oxalate (44,45), respectively. In addition, pork was not to be suggested for Muslims due to religious reasons.…”
Section: Content Credibilitymentioning
confidence: 99%